Circulating miRNAs are associated with the systemic extent of atherosclerosis : novel observations for miR-27b and miR-146 - Pereira da Silva, Tiago (2021)
Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).